Metode Fuzzy Mamdani Pada Sistem Pendukung Keputusan Penentuan Jumlah Petugas BPBD Takengon - Satria, Budy; FAJAR, LM; Efitra, Efitra; Efendi, Irman (Generation Journal, 2021)
To determine the number of officers at the Regional Disaster Management Agency (BPBD), the results of the Fuzzy calculations 2020. In May there are 70 requests for officers, while the number of existing officers is 109 and possibly 95. In June the requests for officers are 80, while the existing officers are 90 and possibly 87. In July the requests for officers are 90 , while the existing officers numbered 75 and possibly 72 were assigned. Until September the request for officers was 40, the existing officers were 58 and possibly 41 were assigned. Tests were also carried out using matlab tools as a form of implementation in order to get accurate results according to with manual calculation of the Fuzzy mamdani method.